THE ROLE OF HUMAN CAPITAL IN DRIVING STRATEGY HUMAN CENTRIC MARKETING: A SYSTEMATIC LITERATURE REVIEW - Lestari, Dian Mahardi; MN, Iman Hasan Ansari (Penelitian dan Pengembangan Ilmu, 2025)
This research aims to explore the strategic role of human capital in encouraging the implementation of human centric marketing strategies in the modern organizational environment. Through a systematic literature review (SLR) approach, this study examined 10 scientific articles obtained from the Emerald, Elsevier, and Google Scholar databases, with a publication year range of 2016 to 2024. The selection process is carried out based on inclusion criteria in the form of topic suitability, empirical evidence,and full accessibility to the article. The results of the analysis show that human capital,which includes individual knowledge, skills, and values, has a significant role in creating a company's competitive advantage through improving customer experience, service innovation, and consumer loyalty. Sustainable human resource development has proven to be the main foundation in the success of a customer-oriented marketing strategy. This study provides important implications for practitioners and policymakers to prioritize investment in human capital development to strengthen human-focused marketing strategies in the long term.